Modern Postcolonial Readings of the English Literary Canon: Theoretical Controversies and Implications - Ciglar-Žanić, Janja (Array, 1998)
The discussion will engage with the key theoretical issues and controversies surrounding the postcolonial theory-based readings of literary texts of the Western canon. It will center on the implications of Said's concept of "contrapuntal reading" for cultural and literary criticism. In the course of the paper two propositions will be explored: a) that "contrapuntal reading" is capable of activating a simultaneous awareness both of the metropolitan hi/story narrated and of the hi/stories of the Other against and together with which the dominant narrative acts; b) that this critical bi/multi/focality of postcolonialism as a reading strategy can be highly influential in shifting cultural and literary-critical concerns in the direction of the genuine forms of comparative cultural study. The examples will comprise modern postcolonial readings of Shakespeare's plays.